Another look at the relationship between energy consumption, carbon dioxide emissions, and economic growth in South Africa - Bekun, Festus Victor; Emir, Fırat; Sarkodie, Samuel Asumadu (The Science of the total environment, 2019)
This study explores the energy use and economic growth nexus from 1960 to 2016 in South Africa while accounting for capital, labour, and carbon dioxide emissions. We applied Bayer and Hanck (2013) combined co-integration approach, Pesaran et al. (2001) bounds test and Kripfganz and Schneider (2018) critical values and approximate p-values. The empirical evidence finds support for a long-run equilibrium relationship among investigated variables. The Granger causality test indicates one-way causality from energy use to economic growth, validating the energy-led growth hypothesis. Our study found an inverted U-shaped pattern between energy use and economic growth in the long run. This finding suggests that at a higher level of economic development there is less intensification of energy consumption, hence, signifying a decline in energy intensity while validating energy efficiency in South Africa. [Display omitted] •A unidirectional causality is observed from energy consumption to CO2 emissions.•The results validate the energy-induced growth hypothesis in South Africa•Economic growth and carbon dioxide emission exhibits an inverse relationship.•Decoupling economic growth from energy use needed to achieve energy efficiency